How can oral and maxillofacial surgery units best support second degree students?. Issue 10 (December 2020) - Rowe, A.; Sharp, I.
Abstract: Returning to study for a second degree to enter higher OMFS training often leaves students feeling 'out in the wilderness'. Many OMFS units are keen to support these students and make use of their skills and enthusiasm by employing them. Often there are barriers to students and units working together. We have explored some of these barriers by surveying second-degree students (both medical and dental) to see what simple measures OMFS units can take to improve their support for students. From the survey we have devised a list of Essential and Desirable criteria to assist OMFS units in supporting students, aiming to have a positive effect on retention through the challenging but necessary period of the second degree.